Dynamics of Service Quality, Customer Satisfaction and Loyalty: A Study of the Retail Banking Industry of Sri Lanka - Fernando, Mayuri A.; Wijetunga, Dinuka (My University, 2003)
The importance of customer loyalty for business success has been well documented in marketing literature. While satisfaction was considered for a long time as the key to customer retention, this assumption has been questioned in recent years. In services marketing, much attention has been paid to customers’ perceived service quality and satisfaction as antecedents of loyalty. The study reveals that in the retail banking sector of Sri Lanka, satisfaction, while being a necessary condition for loyalty, is not a sufficient condition in inducing it. While dissatisfied customers show definite switching tendencies, satisfaction does not guarantee loyalty. Functional quality (in comparison to technical quality and tangibles) is found to be the best discriminator between satisfied and dissatisfied customers. However, service quality fails to explain the differences between loyal customers and switchers among the satisfied customers. Thus, it is concluded that in the Sri Lankan retail banking sector, service quality affects loyalty via satisfaction. However, in converting satisfied customers into loyal customers, marketers have to look beyond service quality.